High-Salt Enhances the Inflammatory Response by Retina Pigment Epithelium Cells following Lipopolysaccharide Stimulation. (10th December 2015) - Zhang, Dike; Wang, Chaokui; Cao, Shuang; Ye, Zi; Deng, Bolin; Kijlstra, Aize; Yang, Peizeng
Abstract : High-salt has been shown to play a role in the pathogenesis of autoimmune disease. In this study, we investigated the effect of high-salt on the production of inflammatory mediators by ARPE-19 cells and the possible mechanisms involved. ARPE-19 cells were cultured with LPS in DMEM to which extra NaCl had been added (20 mM and 40 mM). NaCl had no influence on the apoptosis and proliferation of ARPE-19. Addition of 40 mM NaCl significantly induced IL-6 and MCP-1 production but had no effect on IL-8 secretion. High mannitol, as an osmotic stress control, did not affect the secretion of inflammatory mediators by ARPE-19 cells indicating that the effect was not mediated by osmolarity. Coculture of ARPE-19 cells with NaCl resulted in significant increases in the phosphorylation of p38 MAPK, Akt, and NF- κ B and an upregulation of the transcription factors NFAT5 and SGK1. High-salt significantly promotes IL-6 and MCP-1 production by ARPE-19 cells and is associated with activation of the p38 MAPK, Akt, and NF- κ B pathway and NFAT-SGK1 pathways.